Biological half-life of radioactive cesium in Japanese rockfish Sebastes cheni contaminated by the Fukushima Daiichi nuclear power plant accident. (December 2015) - Matsumoto, Akira; Shigeoka, Yu; Arakawa, Hisayuki; Hirakawa, Naoto; Morioka, Yoshiaki; Mizuno, Takuji
Abstract: Since the Fukushima accident in March 2011 the concentration of radioactive cesium in Japanese rockfish ( Sebastes cheni ) has been decreasing slower than other fish species. The aim of this study was therefore to investigate the possibility of slow elimination rate (i.e., relatively longer T b ) as one of the reasons for the slow decrease in 137 Cs concentrations in Japanese rockfish ( S. cheni ). To do this, we reared twenty-three individuals of this species for a period of about 1 year, during which time we measured the 137 Cs concentrations and γ-ray spectra 14 times by using a high-efficiency NaI(Tl) scintillator. We then examined the relationship between the 137 Cs concentrations and the total length of each individual. We estimated the biological half-life ( T b, day) for each individual using the total number of 137 Cs counts in the energy region, and examined the effects of total length and 137 Cs concentration on T b by generalized linear model (GLM). We also examined the effect of sex, total length, seawater temperature, and the 137 Cs concentration of seawater on temporal changes in the 137 Cs count reduction rate by GLM. There was no clear relationship between the corrected whole-body 137 Cs concentrations and the total length in females, however there was a significant positive correlation between these two variables in males. The difference between males and females may be attributable to variation in the degree of dilution because of variable growth of individuals, and suggests that the 137 Cs concentrations of small individuals may be greatly diluted because of faster growth. However, there was no significant difference in T b between sexes. The mean T b (±SD) in all individuals was 269 (±39) days; this T b value is 2.7–5.4 times longer than past T b values (marine fish: 50–100 days), and is thought to be one of the reasons for the slower decrease in 137 Cs concentrations in this species than other fish species on the coast of Fukushima. The GLM showed significant effects of both total length and 137 Cs concentration on T b, which may reflect a reduction in the metabolic rate with increased body size (i.e., aging) and gradient of concentration against seawater. The GLM also showed a significant positive effect of seawater temperature on the reduction rate of the 137 Cs counts ( D, day −1 ). Therefore, D was clearly related to seasonal variations in the temperature of seawater, and this relationship may be attributable to changes in the metabolic rate that are controlled by variations in the seawater temperature. From these measurements, we examined the processes that control reductions in 137 Cs radioactivity. Highlights: In this study, we established a long-term (1-year) method for measuring radioactive cesium in living Japanese rockfish using a high-efficiency NaI(Tl) scintillator. We estimated the biological half-life ( T b, day) for each individual. The mean T b (±SD) in all individuals was 269 (±39) days; this T b value is 2.7–5.4 times longer than past T b values of marine fish. The reduction rate of the 137 Cs counts ( D, day −1 ) was clearly related to seasonal variations in the temperature of seawater, and this relationship may be attributable to changes in the metabolic rate that are controlled by variations in the seawater temperature.